THE ANALYSIS OF THE IMPACT OF MARKETING MIX TOWARD SOFTWARE PURCHASE INTENTION IN RELATION TO SOFTWARE PIRACY IN INDONESIA - Santoso, Aditya; Sungkari, Hari Santosa (Bina Nusantara University, 2013)
This thesis type is research with the subject of marketing mix. The study discusses issues of software piracy in Indonesia. Goal of this research is to provide information whether the marketing mix strategy (Product, Price, Promotion, Place) influencing consumer purchase intention that lead to reducing software piracy in Indonesia, and hope this thesis can be used by software principal to reduce piracy and get benefits from this strategy. Literature of this thesis is taken mostly from International book, and several took from local book, local trusted magazine, and best internet source. Theory of marketing mix, purchase intention, software history, software piracy, type of piracy, and the legal use of software has been included to this thesis to give more understanding to the reader. It took the field research on people who use pc / notebook and have used pirated software before, total of 19 questions have been responded by 100 respondents using accidental sampling.Â This thesis also examines the impact of marketing mix toward software purchase intention. Using regression analysis, it can be found that there are two variables: price and place that have positive correlation toward software purchase intention. The result of the study will help the principal company to create the right strategy to reduce piracy in Indonesia software market.